2016
DOI: 10.1007/s11802-016-3043-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of periodical salinity fluctuation on the growth, molting, energy homeostasis and molting-related gene expression of Litopenaeus vannamei

Abstract: To determine the response of Litopenaeus vannamei to periodical salinity fluctuation, a 30-day experiment was conducted in laboratory. In this experiment, two salinity fluctuation amplitudes of 4 (group S4) and 10 (group S10) were designed. The constant salinity of 30 (group S0) was used as the control. Levels of shrimp growth, molting frequency (MF), cellular energy status (ATP, ADP and AMP), as well as the expression of genes encoding molt-inhibiting hormone (MIH), crustacean hyperglycemic hormone (CHH), ecd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This may also be due to differences in water transparency caused by variations in the plankton and organic matter content in the aquaculture water, resulting in different survival and development effects of juvenile C. quadricarinatus under the same light conditions, as demonstrated in the two studies, which warrants further investigations in the future. Nevertheless, it is important to mention that in additional studies concerning crustaceans, yellow light has been demonstrated to enhance the survival rate of Pacific white shrimp (L. vannamei) and expedite the growth of swimming crab (Portunus trituberculatus) juveniles [13,28]. Conversely, red light has been found to be detrimental to the growth, development, and survival of giant freshwater prawn (M. rosenbergii) and Amazon river prawn (Macrobrachium amazonicum) [12,29].…”
Section: Discussionmentioning
confidence: 99%
“…This may also be due to differences in water transparency caused by variations in the plankton and organic matter content in the aquaculture water, resulting in different survival and development effects of juvenile C. quadricarinatus under the same light conditions, as demonstrated in the two studies, which warrants further investigations in the future. Nevertheless, it is important to mention that in additional studies concerning crustaceans, yellow light has been demonstrated to enhance the survival rate of Pacific white shrimp (L. vannamei) and expedite the growth of swimming crab (Portunus trituberculatus) juveniles [13,28]. Conversely, red light has been found to be detrimental to the growth, development, and survival of giant freshwater prawn (M. rosenbergii) and Amazon river prawn (Macrobrachium amazonicum) [12,29].…”
Section: Discussionmentioning
confidence: 99%
“…In pond culture systems, multiple studies have shown that the N and P utilization rates by cultured organisms are generally low, within 18.1-36.9% and 9.4-23.1%, respectively (Hu et al, 2013;Li et al, 2012;Wang et al, 2018;Zhang et al, 2011Zhang et al, , 2015Zhao, Xu, et al, 2021;Zhao, Zhong, et al, 2021). In this study, the N utilization rate was 19.5-27.7% and the P utilization rate was 26.4-37.5%, which may be affected by culture objectives and modes.…”
Section: Utilization Of N and P By Cultured Organismsmentioning
confidence: 99%
“…Vitamin C exists mainly in humans in the form of reduced ascorbic acid, while compared with most vertebrates, and humanoid primates (including humans), but it cannot be synthesized by itself and can only be ingested through food [5].…”
Section: Vitamin Intake and Synthesismentioning
confidence: 99%